La Dactilopintura en el Desarrollo Motriz, de los niños y niñas de Primero de Inicial del Centro Infantil del Buen Vivir “Carlos Guido Cattani”, del cantón Alausí, provincia de Chimborazo durante el año lectivo 2015-2016 - Guevara Tapia, Diego Alonso (2016)
This research work was carried out at the Centro Infantil del Buen Vivir “Carlos Guido Cattani”, which is located in Alausí canton, Chimborazo Province. The topic of this investigation is The Finger painting in Motor Development of boys and girls of primero de inicial del Centro Infantil del Buen Vivir “Carlos Guido Cattani”, from Alausí canton, Chimborazo province, during the 2015-2016 academic year. It was identified the existing problem in the Institution. The necessary literature that serves as theoretical basic was consulted. Then, the information is collected by applying the observation sheet, which has been analyzed and quantified and it was reached the conclusions and recommendations. Where it is determined, the urgent need to incorporate finger painting as an active technique to develop the motor area in the boys and girls, giving the teacher the opportunity to implement innovative activities inside and outside the classroom, at the same time these data allowed to test the hypothesis. It is also evidenced that there are similar but with different research proposals, so it is a cause of concern to teachers of this level of education.